2022
DOI: 10.1016/j.ymthe.2021.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose replicating poxvirus vector-based RBD vaccine drives robust humoral and T cell immune response against SARS-CoV-2 infection

Abstract: The coronavirus disease 2019 (COVID-19) pandemic requires the continued development of safe, long-lasting, and efficacious vaccines for preventive responses to major outbreaks around the world, and especially in isolated and developing countries. To combat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), we characterize a temperature-stable vaccine candidate (TOH-Vac1) that uses a replication-competent, attenuated vaccinia virus as a vector to express a membrane-tethered spike receptor binding dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 93 publications
(125 reference statements)
1
30
0
2
Order By: Relevance
“…[A] replication within the TME -using mouse models and patient-derived tumour explants, we have shown that VV has an inherent ability to attack aspects of the TME including the tumour neo-vasculature (34) and certain CAF populations (35); [B] the capacity to encode large and multiple therapeutic transgenes (5); [C] extensive clinical knowledge of the viral vector safety due to its use as a vaccine to eradicate smallpox (5) and treat other diseases (36,37), and [D] oncolytic VV can be selectively delivered to CRC tumours by IV administration (38) and clinical trials have demonstrated safety in CRC patients (38,39). Systemic delivery of therapeutics is of particularly importance for CRC treatment as many patients present with locally advanced or metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[A] replication within the TME -using mouse models and patient-derived tumour explants, we have shown that VV has an inherent ability to attack aspects of the TME including the tumour neo-vasculature (34) and certain CAF populations (35); [B] the capacity to encode large and multiple therapeutic transgenes (5); [C] extensive clinical knowledge of the viral vector safety due to its use as a vaccine to eradicate smallpox (5) and treat other diseases (36,37), and [D] oncolytic VV can be selectively delivered to CRC tumours by IV administration (38) and clinical trials have demonstrated safety in CRC patients (38,39). Systemic delivery of therapeutics is of particularly importance for CRC treatment as many patients present with locally advanced or metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…We selected a modified oncolytic Copenhagen strain of vaccinia virus (VV; ClinicalTrials.gov: NCT04301011 and patent publication 20220056480) as a therapeutic vector based on its ability to infect and kill human and murine CRC cell lines as spheroid models more efficiently than other oncolytic viruses. VV also has many desirable features which include, but are not limited to: [A] replication within the TME - using mouse models and patient-derived tumour explants, we have shown that VV has an inherent ability to attack aspects of the TME including the tumour neo-vasculature ( 34 ) and certain CAF populations ( 35 ); [B] the capacity to encode large and multiple therapeutic transgenes ( 5 ); [C] extensive clinical knowledge of the viral vector safety due to its use as a vaccine to eradicate smallpox ( 5 ) and treat other diseases ( 36 , 37 ), and [D] oncolytic VV can be selectively delivered to CRC tumours by IV administration ( 38 ) and clinical trials have demonstrated safety in CRC patients ( 38 , 39 ). Systemic delivery of therapeutics is of particularly importance for CRC treatment as many patients present with locally advanced or metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need to develop alternative VACV vectors to improve their immunogenicity. Two replication-competent recombinant VACV-based COVID-19 vaccine candidates have been reported to protect hamsters against SARS-CoV-2 challenge after single-dose immunization ( 15 , 46 ). One of the replication-competent VACV/COVID-19 vaccine candidates was based on the VACV NYCBH strain (the parental strain of ACAM2000 used in this study), in which the SARS-CoV-2 spike gene was inserted into the TK gene locus ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the replication-competent VACV/COVID-19 vaccine candidates was based on the VACV NYCBH strain (the parental strain of ACAM2000 used in this study), in which the SARS-CoV-2 spike gene was inserted into the TK gene locus ( 15 ). Another one was based on the VACV TianTan (TT) strain, in which the RBD of the spike protein was expressed from the B14 locus ( 46 ). The latter study also demonstrated that the replication-competent VACV TT-based vaccine candidate was significantly more immunogenic than the MVA-based counterpart in inducing both antibody and T-cell responses ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation